2020
DOI: 10.1088/1674-4926/41/1/011901
|View full text |Cite
|
Sign up to set email alerts
|

Strain tunable quantum dot based non-classical photon sources

Abstract: Semiconductor quantum dots are leading candidates for the on-demand generation of single photons and entangled photon pairs. High photon quality and indistinguishability of photons from different sources are critical for quantum information applications. The inability to grow perfectly identical quantum dots with ideal optical properties necessitates the application of post-growth tuning techniques via e.g. temperature, electric, magnetic or strain fields. In this review, we summarize the state-of-the-art and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…In experiments, such as achieving a tensile biaxial strain of 6%, in-plane biaxial strain is generated by applying a certain voltage to the piezoelectric ceramic substrate. 69 In addition, by using substrates with different lattice mismatches, a tensile biaxial strain of 6% can be achieved. Due to the lattice mismatch of the heterojunction being only 0.11%, applying biaxial strain to the heterojunction is equivalent to applying biaxial strain to the two monolayers, respectively.…”
Section: (B) and (C)mentioning
confidence: 99%
“…In experiments, such as achieving a tensile biaxial strain of 6%, in-plane biaxial strain is generated by applying a certain voltage to the piezoelectric ceramic substrate. 69 In addition, by using substrates with different lattice mismatches, a tensile biaxial strain of 6% can be achieved. Due to the lattice mismatch of the heterojunction being only 0.11%, applying biaxial strain to the heterojunction is equivalent to applying biaxial strain to the two monolayers, respectively.…”
Section: (B) and (C)mentioning
confidence: 99%
“…In addition, a discussion of the prospects and challenges of deploying the strain engineering technique for future scalable quantum networks and photonic quantum circuits was also presented. Yang and co-workers [51] emphasized that inability to grow perfectly identical quantum dots with ideal optical properties necessitates the application of post-growth tuning techniques via, e.g., temperature, electric, magnetic, or strain fields. They showed that the wavelength of single photons and entangled photon pairs emitted by InGaAs/GaAs quantum dots can be reversibly tuned using piezoelectric crystals such as PMN-PT [51].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Yang and co-workers [51] emphasized that inability to grow perfectly identical quantum dots with ideal optical properties necessitates the application of post-growth tuning techniques via, e.g., temperature, electric, magnetic, or strain fields. They showed that the wavelength of single photons and entangled photon pairs emitted by InGaAs/GaAs quantum dots can be reversibly tuned using piezoelectric crystals such as PMN-PT [51]. For electrical triggering and tuning of the wavelength or the exciton's fine structure, they used quantum light-emitting diodes.…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for some time now that the fine structure splitting of the HH exciton can be changed, and even made to vanish, by applying an in-plane stress [56]; a model evaluating the effect of the Bir and Pikus Hamiltonian on the electron-heavy hole exchange has been proposed in Ref. [57].…”
Section: Vi23 Electron-hole Exchangementioning
confidence: 99%